2015
DOI: 10.1159/000381420
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception of Imiquimod Treatment for Actinic Keratosis and Superficial Basal Cell Carcinoma in 202 Patients

Abstract: Objective: To document the impact on patient-reported outcomes and health-related quality of life (HRQoL) of treatment with imiquimod cream in patients with actinic keratosis (AK) and superficial basal cell carcinoma (sBCC). Methods: This open-label, multicenter study included AK and sBCC patients eligible for treatment with imiquimod 5% cream. HRQoL was measured by the Skindex-17 and the Skin Cancer Index (SCI) and treatment satisfaction by the Treatment Satisfaction Questionnaire for Medication. Results: 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Topical application of imiquimod induces IFNα within AK lesions and subsequently triggers such innate and adaptive immune response 19. An open-label, multicenter study with 118 AK patients utilized the Skin-dex-17 and TSQM surveys to assess how treatment with imiquimod cream 5% impacts patient-reported outcomes and health-related QoL (HRQoL) and found no clinically relevant impact 20. However, HRQoL impairment was noted to be low even at baseline for both surveys 20.…”
Section: Topical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical application of imiquimod induces IFNα within AK lesions and subsequently triggers such innate and adaptive immune response 19. An open-label, multicenter study with 118 AK patients utilized the Skin-dex-17 and TSQM surveys to assess how treatment with imiquimod cream 5% impacts patient-reported outcomes and health-related QoL (HRQoL) and found no clinically relevant impact 20. However, HRQoL impairment was noted to be low even at baseline for both surveys 20.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…An open-label, multicenter study with 118 AK patients utilized the Skin-dex-17 and TSQM surveys to assess how treatment with imiquimod cream 5% impacts patient-reported outcomes and health-related QoL (HRQoL) and found no clinically relevant impact 20. However, HRQoL impairment was noted to be low even at baseline for both surveys 20. Although literature assessing patient satisfaction with imiquimod as a treatment for AK is limited, various studies compare patient QoL and preference between imiquimod and other treatments.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Health-related QoL was investigated in a study of 118 AK subjects treated with imiquimod 0.05% cream for 8 weeks, in which QoL was assessed using a Skindex-16 survey and the Skin Cancer Index. 15 The small improvements in QoL seen at week 8 were judged to be lacking in clinical relevance. Low baseline impairments in QoL may have limited the ability to detect more robust improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies have demonstrated unchanged or even decreased QoL despite excellent treatment outcomes. 15 , 16 Recently, a post hoc, exploratory analysis of AK subjects enrolled in Phase 3 clinical trials involving ingenol mebutate gel found that this therapy was associated with significant improvements in QoL. 17 Here, we report the results of QoL assessments from a prospective clinical study in subjects with AKs of the face who were treated with ingenol mebutate gel 0.015% for three consecutive days.…”
Section: Introductionmentioning
confidence: 96%
“…Only four studies were clinical trials. 10,[23][24][25] Investigations were designed prevalently as national studies (10/14) 6,8,10,12,[15][16][17]22,23,26 and carried out in North America, 10,15 Europe, 8,16,17,22,26 South America, 6,23 and Australia. 12 Brazil was the only represented South American country, 6,23 and no data were present to represent Asian and African countries.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%